Assimilation in Wahrani Dialect of Algerian Arabic: A Non-Linear Analysis - بلجنة، أمال عبدالقادر; المحادين، رضوان سالم (جامعة جرش, 2024)
تبحث هذه الدراسة في الأنواع المختلفة لعمليات التماثل الصوتي في اللهجة الوهرانية، وهي لهجة عربية جزائرية تتواجد في الغرب الجزائري. يستخدم الباحث التسجيلات والملاحظات الميدانية للحديث العفوي للمتحدثين في سياق طبيعي كبيانات للدراسة. تم تحليل البيانات باستخدام الأساليب غير الخطية لعلم الفونولوجية والتحليل الهندسي للأصوات المميزة حيث أثبتت أنها مناسبة في العديد من الدراسات من أجل شرح وتحليل العمليات الفونولوجية. كشف تحليل البيانات أن العمليات الفونولوجية المتواجدة في اللهجة الوهرانية هي التالية: التماثل الصوتي المحلي، البعيد، الجزئي، الكلي، التراجعي وأخيرا المتقدم. تناقش الدراسة التماثل الصوتي ل/ ال/ التعريف، والتماثل الصوتي الإدغامي لحرف النون، كما تناقش الدراسة التماثل الصوتي بين الأصوات المجهورة والأصوات الغير مجهورة، وأخيرا تتداول الدراسة التماثل الصوتي للأصوات المفخمة. The study investigates the different types of assimilation of Wahrani dialect, an Algerian Arabic dialect spoken in the north-western region of Algeria. The researcher uses recordings and field notes of spontaneous speech of native speakers in a natural context as data for the study. The data is analyzed using the non-linear approaches of autosegmental phonology and feature geometry as they have proven adequate in numerous studies for the better explanation and analysis of the phonological process of assimilation. The study indicates that Wahrani dialect displays almost all types of assimilation: local and long-distance assimilation, partial and total assimilation, and regressive and progressive assimilation processes. The study discusses the assimilation of the definite article/l/, the assimilation of sonorants, voice assimilation, nasal homorganic assimilation, vowel harmony and finally emphasis assimilation.
Keywords: التماثل الصوتي -- اللهجة الوهرانية -- العمليات الفونولوجية -- عملية الاستيعاب